Effect of different preservation processes on chemical composition and fatty acid profile of anchovy (Engraulis anchoita) - Czerner, Marina (2015)
The effects of salting-ripening, canning and marinating processes on chemical composition and fatty acid profile of anchovy (Engraulis anchoita) were evaluated (p = 0.01), with emphasis on long-chain polyunsaturated fatty acids. Fresh anchovy showed a high proportion of PUFAs (∼45 g/100 g total lipid) with an eicosapentaenoic (EPA) + docosahexaenoic (DHA) content of 27.08 g/100 g total lipid. The salting-ripening process led to the largest changes in the chemical composition and the fatty acid profile, which resulted in a reduction of ∼70% on the total EPA and DHA contents (g/100 g edible portion). Contrary, canned and marinated anchovy presented a fatty acid profile similar to that of fresh anchovy. The use of vegetable oil as covering liquid led to final products with increased ω-6 PUFAs content. Despite the modifications observed, the total amount of essential EPA and DHA fatty acids provided by these products remained high compared with values reported in literature for other foods.